2021
DOI: 10.3389/fpubh.2020.613250
|View full text |Cite
|
Sign up to set email alerts
|

Adequate Utilization of Emergency Services in Germany: Is There a Differential by Migration Background?

Abstract: Background: The role of emergency services (ES) is to provide round-the-clock acute care. In recent years, inadequate use of ES has been internationally thematised because of overcrowding and the associated cost. Evidence shows that migrant populations tend to use more ES than non-migrant but it remains to show if there is a differential in inadequacy.Method: Quantitative data from consecutive patients visiting three ES in Berlin (hospital-based outpatient clinics for internal medicine or gynecology) from July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
9
0
5
Order By: Relevance
“…Limited health literacy was also demonstrated for people with migration background (3) and there is evidence for higher use of emergency services among migrants compared to non-migrants across Europe (25). A recent German study found that migrants show lower odds of adequate emergency department use compared to non-migrants (26). Our results indicate that a lack of knowledge especially of the medical on call service among people with a migration background may in part explain these differences.…”
Section: Discussionmentioning
confidence: 50%
“…Limited health literacy was also demonstrated for people with migration background (3) and there is evidence for higher use of emergency services among migrants compared to non-migrants across Europe (25). A recent German study found that migrants show lower odds of adequate emergency department use compared to non-migrants (26). Our results indicate that a lack of knowledge especially of the medical on call service among people with a migration background may in part explain these differences.…”
Section: Discussionmentioning
confidence: 50%
“…Against the background of the current organisation of urgent and emergency care services in Germany, the present study introduces the individual predisposing factors sex, age, education, migration background and having children into the analyses of utilisation. Predisposing factors as lower education and a migration background are often associated with more frequent or inadequate prehospital and hospital emergency care utilisation in Germany and further European countries,7 23–26 although some current findings for Germany did not confirm these inequalities 27–29. Moreover, higher age predicts increased ED use while sex does not seem to play a significant role 7 24 27 28.…”
Section: Introductionmentioning
confidence: 68%
“…Additionally, the daytime plays an important role for symptoms like that. Overall, measurement of adequate utilisation is very diverse and remains difficult 7 23 47 63. Thus, interpretations should be done carefully.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a non-interventional cross-sectional study [ 8 ], factors influencing patients’ utilization of hospital emergency departments (EDs) were assessed and analyzed with a focus on how satisfied physicians were with the doctor–patient interactions (DPIs). We collected data from three sources: 1) standardized questionnaire-based interviews with patients, 2) short questionnaires for attending physicians concerning the DPI, 3) evaluation of the patient’s medical report from the ED.…”
Section: Methodsmentioning
confidence: 99%
“…We used four parameters to determine appropriate ED utilization. ED utilization was defined as appropriate if the patient had been admitted as an inpatient (criterion A), or/and if all three of the following criteria were met: 1) patient indicates a treatment urgency of at least 7 out of 10 as well as 2) a pain intensity of at least 7 out of 10, and 3) the decision to seek emergency medical care was made by a physician (criterion B) [ 8 ]. The patients were asked to assess their perceived urgency and intensity of pain using an 11-point Likert scale (from 0 = “no urgent need for treatment” to 10 = “very urgent; imminent danger to life”/from 0 = “no pain at all” to 10 = “unbearable pain”).…”
Section: Methodsmentioning
confidence: 99%